Sensory Evaluation of Chhana Burfi Process with Jackfruit (Artocarpus hetrophyllus L.) Pulp - Dhawade, A. S.; Patil, V. N.; Terde, S. H.; Dandekar, V. S.; Ramod, S. S.; Mayekar, A. J.; Dhopavkar, R. V. (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted at Dept. of Animal Husbandry and Dairy Science, Dr. BSKKV, Dapoli, Ratnagiri, Maharashtra, India during August 2021 to May 2022 to evaluate the suitability of Jackfruit pulp as flavouring agent in developing flavoured Chhana Burfi and its production cost. Basically, Cow milk required for preparation of Chhana, Citric acid used for Coagulation of milk, Sugar and Jackfruit pulp etc. was required to conduct this research. The curd mass obtained when milk is coagulated with the organic acids such as citric acid at higher temperature and after subsequent drainage of whey, mass of curd obtained is called chhana. Chhana was used as base material for preparation of chhana burfi. The Chhana Burfi was prepared from cow milk by incorporating jackfruit pulp @ 10% (F1), 15% (F2), and 20% (F3) and two sugar level i.e. 15% (S1) and 18% (S2) On the basis of weight of Chhana. All treatment is analyzed for sensory characteristic i.e. colour and appearance, body and texture, flavour and overall acceptability by using 9-point Hedonic scale. Present study investigated that jackfruit pulp could be successfully utilized for preparation of flavoured chhana burfi. The most acceptable quality flavour Chhana Burfi could be prepared by using 15% jackfruit pulp and 18% sugar. Prepared delicious milk product i.e. Jackfruit flavour Chhana Burfi rich taste and flavour along with nutritional value. The production cost of Jackfruit flavour Chhana Burfi (most acceptable level i.e.S2F2) was Rs. 355.8/- per kg.